1978
DOI: 10.1093/ajcp/69.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biologic Sources of Variation of Leukocyte Counts and Other Hematologic Quantities Using Very Precise Automated Analyzers

Abstract: The authors determined mean day-to-day (daily over five days), mean week-to-week (weekly over five weeks) and mean hour-to-hour (800 h, 1100 h, 1400 h) physiologic intra-individual variation of concentration values of leukocyte cell types, platelet count, and erythrocyte values (hematocrit, hemoglobin) for a group of 20 healthy adult volunteers. Total leukocyte counts and concentration values of leukocyte cell types were determined in duplicate on the Hemalong-DTM Automated Leukocyte Differential Cell Counter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 0 publications
1
34
0
1
Order By: Relevance
“…While studying the literature on the intra-individual variability of haematological data, our attention was drawn to two papers by Statlandet al (3,4). Comparison of our results with data from the literature (tab.8) could not be made for the critical differences, äs these have not been reported before in this field.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…While studying the literature on the intra-individual variability of haematological data, our attention was drawn to two papers by Statlandet al (3,4). Comparison of our results with data from the literature (tab.8) could not be made for the critical differences, äs these have not been reported before in this field.…”
Section: Discussionmentioning
confidence: 65%
“…There has been an especial improvement in the precision of the differential count, mainly due to the fact that the analyser screens about 10000 leukocytes in each analysis (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…1 Our results are slightly different from the previously published observations, which showed hour-to-hour and subject-specific diurnal fluctuation. 5,6 For example, the study by Sennels et al 5 demonstrated diurnal variation of hematology parameters. In this study, samples were collected every third hour through 24 hours, 9 time points in total, in contrast to 3 time points during an 8-hour interval in our study.…”
Section: Determination Of the Rcv Or Critical Differencementioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Some parameters, such as hemoglobin or reticulocytes, have been demonstrated to exhibit hour-to-hour, day-to-day, or seasonal intraindividual fluctuation. 3,6 We revisit these areas for several reasons. First of all, we use the newest model of automated hematology analyzer, UniCel DxH 800 (Beckman Coulter, Inc, Fullerton, California).…”
mentioning
confidence: 99%
See 1 more Smart Citation